2014
DOI: 10.1007/s40279-014-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statin Medications on Aerobic Exercise Capacity and Training Adaptations

Abstract: The incidence of myopathy increases dramatically in statin users who also exercise, likely limiting the positive impact of this lifesaving medication. New evidence also indicates that statin use can directly compromise aerobic exercise capacity; however, we are just beginning to understand the interactions of statins with exercise training and adaptations. This review focuses on the interactions of statins with aerobic exercise capacity and training adaptations to summarize the available information and draw a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 96 publications
0
9
0
4
Order By: Relevance
“…It has been demonstrated that metformin may attenuate the beneficial effects of exercise on glucose regulation, blood pressure, and blood lipid profile (Malin & Braun, 2016). Similarly, studies suggest that statins may attenuate exercise-induced adaptations as well (Mikus et al, 2013;Murlasits & Radak, 2014), although the opposite effect has also been observed (Meex et al, 2010). As our study was not sufficiently powered for a between-participant statistical comparison of the training adaptations in participants who were taking statins and/or metformin (n=12) vs. the participants who were not (n=4), we cannot determine whether the use of medication may have affected the response to training in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that metformin may attenuate the beneficial effects of exercise on glucose regulation, blood pressure, and blood lipid profile (Malin & Braun, 2016). Similarly, studies suggest that statins may attenuate exercise-induced adaptations as well (Mikus et al, 2013;Murlasits & Radak, 2014), although the opposite effect has also been observed (Meex et al, 2010). As our study was not sufficiently powered for a between-participant statistical comparison of the training adaptations in participants who were taking statins and/or metformin (n=12) vs. the participants who were not (n=4), we cannot determine whether the use of medication may have affected the response to training in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is possible that the inclusion of statin‐treated individuals in this study may have impaired our ability to detect improvements in skeletal muscle oxidative capacity and reduction mitochondrial ROS production following RET (Murlasits and Radak ). There were no significant differences in the changes in skeletal muscle oxidative capacity or mitochondrial ROS production in the statin users and non‐users following RET in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although many patients with HF receive statins, and the use of ET interventions are increasingly incorporated into a patient-centered treatment approach, guidelines do not provide specific recommendations for a combined use strategy or appropriate timing for initiating ET and statin therapy (6,7). …”
mentioning
confidence: 99%